2019
DOI: 10.30845/ijbss.v10n5p7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Equity Finance on Financial Performance of Small and Medium Enterprises in Kenya

Abstract: All business enterprises are mostly acknowledged as an important contributor of poverty eradication and increasing economic growth all over the world. Despite the role of SMEs in building economic development in Kenya, they are facing several challenges among them being choosing the best source of finance for their successful performance. Purposely this study was to determine the effect of sources of finance on financial performance of small and medium sized enterprises in Kenya. The specific objectives were; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…We found comparatively larger effect sizes for studies that examined micro-sized firms (r̅ c= 0.6203, k = 7) than for those investigating small and medium sized enterprises (SMEs) (r̅ c = 0.4030, k = 69), as well as mixed-sized firms (r̅ c = 0.5524, k = 56), and large firms (r̅ c = 0.1279, k = 15). Regarding controlling for publication bias, we found considerably larger effect 17 r̅ c denotes reliability corrected random-effect mean effect size.…”
Section: Bivariate Analysismentioning
confidence: 77%
“…We found comparatively larger effect sizes for studies that examined micro-sized firms (r̅ c= 0.6203, k = 7) than for those investigating small and medium sized enterprises (SMEs) (r̅ c = 0.4030, k = 69), as well as mixed-sized firms (r̅ c = 0.5524, k = 56), and large firms (r̅ c = 0.1279, k = 15). Regarding controlling for publication bias, we found considerably larger effect 17 r̅ c denotes reliability corrected random-effect mean effect size.…”
Section: Bivariate Analysismentioning
confidence: 77%
“…However, the findings related to the link between equity capital and financial performance are inconsistent. For instance, while Cheruyot and Ntoiti (2015) as well as Nasimi (2016) established a negative and significant relationship between equity and firm performance, Taani (2013), Vatavua (2015), as well as Muturi and Njeru (2019) reported a significant and positive association with all the identified measures of financial performance.…”
Section: Capital Structure and Financial Performancementioning
confidence: 98%
“…Ngatia (2017) applied this theory in the course of analyzing the effects of non-monetary rewards on service provision, and they found that it was significant. Mutie, Muturi, and Njeru (2019), who made use of equity theory when analyzing financial rewards, conducted a similar study in Kenya. Expectations-based rewards can be thought of as being guided by this notion.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%